First report of Angiostrongylus vasorum in an African golden wolf (Canis lupaster) in Algeria - Noureddine Mechouck; Georgiana Deak; Angela Monica Ionică; Corina Toma; Andrada Gabriela Negoescu; Marian Taulescu; Zihad Bouslama; Andrei Daniel Mihalca (Parasites & Vectors)
Abstract Background Angiostrongylus vasorum, commonly known as the “French heartworm,” is a nematode belonging to the Metastrongyloidea superfamily. This parasite was first identified in Toulouse, France in 1853 infecting the pulmonary arteries and the right side of the heart of a Pointer dog. Angiostrongylosis is an important infection due its severe clinical signs and potential for causing high morbidity and mortality in domestic dogs. This nematode has not been studied in Algeria. The aim of this study was investigate the presence of lungworms among different mammal species in a number of Algerian regions. Methods Between February 2022 and September 2023, 47 road-killed animals were collected from six administrative units (departments) in Algeria. All carcasses underwent a full parasitological necropsy, and lung tissues were preserved in 10% buffered formalin and concentrated ethanol for further study. All collected samples were subjected to histological and PCR (cytochrome c oxidase subunit 1 gene) analyses for lungworm identification. Results Histological examination revealed the presence of nematode eggs and larvae in the alveolar space and chronic obstructive vascular changes were detected in a single golden African wolf (Canis lupaster) collected from the department of Constantine. First-stage larvae were collected and morphologically identified as Angiostrongylus spp. The molecular identification confirmed the presence of A. vasorum. All other animals tested were negative for lungworms. Conclusions To the best of our knowledge, this is the first report of A. vasorum infection in an African golden wolf (Canis lupaster). We report a new host association, highlighting the importance of further studies to update the geographical distribution of A. vasorum and its epidemiology across Algeria. Graphical Abstract